Discovery of CYR715: A novel carboxylic acid-containing soluble guanylate cyclase stimulator. (15th May 2021) - Rennie, Glen R.; Barden, Timothy C.; Bernier, Sylvie G.; Carvalho, Andrew; Deming, Renee; Germano, Peter; Hudson, Colleen; Im, G-Yoon J.; Iyengar, Rajesh R.; Jia, Lei; Jung, Joon; Kim, Elise; et al.
Graphical abstract: Abstract: Soluble guanylate cyclase (sGC) is a clinically validated therapeutic target in the treatment of pulmonary hypertension. Modulators of sGC have the potential to treat diseases that are affected by dysregulation of the NO-sGC-cGMP signal transduction pathway. This letter describes the SAR efforts that led to the discovery of CYR715, a novel carboxylic acid-containing sGC stimulator, with an improved metabolic profile relative to our previously described stimulator, IWP-051. CYR715 addressed potential idiosyncratic drug toxicity (IDT) liabilities associated with the formation of reactive, migrating acyl glucuronides (AG) found in related carboxylic acid-containing analogs and demonstrated high oral bioavailability in rat and dose-dependent hemodynamic pharmacology in normotensive Sprague–Dawley rats.